2020
DOI: 10.1126/sciadv.aba0682
|View full text |Cite
|
Sign up to set email alerts
|

Genome integrity and neurogenesis of postnatal hippocampal neural stem/progenitor cells require a unique regulator Filia

Abstract: Endogenous DNA double-strand breaks (DSBs) formation and repair in neural stem/progenitor cells (NSPCs) play fundamental roles in neurogenesis and neurodevelopmental disorders. NSPCs exhibit heterogeneity in terms of lineage fates and neurogenesis activity. Whether NSPCs also have heterogeneous regulations on DSB formation and repair to accommodate region-specific neurogenesis has not been explored. Here, we identified a regional regulator Filia, which is predominantly expressed in mouse hippocampal NSPCs afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…NSPCs are the cellular basis for neurogenesis at fetal and postnatal stages. Accumulations of DNA DSBs and cytosolic double-strand DNA (dsDNA) in NSPCs and their progenies not only impaired neurogenesis and brain functions 28 , 29 , but also evoked innate immune and inflammation responses leading to animal death 30 . Based on the function of Discn in in-vitro cultured NSPCs, we hypothesized that Discn KO might cause accumulations of DSBs and cytosolic dsDNA in brain cells of neonates and adults, and the damages and associated immune responses underlie the newborn death and brain dysfunctions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…NSPCs are the cellular basis for neurogenesis at fetal and postnatal stages. Accumulations of DNA DSBs and cytosolic double-strand DNA (dsDNA) in NSPCs and their progenies not only impaired neurogenesis and brain functions 28 , 29 , but also evoked innate immune and inflammation responses leading to animal death 30 . Based on the function of Discn in in-vitro cultured NSPCs, we hypothesized that Discn KO might cause accumulations of DSBs and cytosolic dsDNA in brain cells of neonates and adults, and the damages and associated immune responses underlie the newborn death and brain dysfunctions.…”
Section: Resultsmentioning
confidence: 99%
“…Many genes critical for neurogenesis in NSPCs harbor RDCs and are susceptible to replication stress-associated perturbations. Thus, replication-associated DNA DSBs in NSPCs directly impacted neurogenesis 29 , 38 , 39 . In addition, DNA DSBs and in particular cytoplasmic dsDNA are able to evoke innate immune response and inflammatory reactions 33 , 40 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, it was recently demonstrated that regional regulator Filia is required for neurodevelopment. In this study, both murine hippocampus and the NSPCs’ research models were used [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Germane to HMZ pathology is the production of reactive oxygen species (ROS), which is implicated in oxidative macromolecular damage, inflammatory response, endoplasmic reticulum (ER) stress and apoptosis [18][19][20][21][22]. The developing brain is especially susceptible to genomic instability and cellular stress engendered by oxidative modification of macromolecules and this is also linked to neurodevelopmental and neurodegenerative diseases including Schizophrenia, Alzheimer's (AD) and Parkinson's (PD) diseases [23][24][25][26][27]. Interestingly, reports by Thiam et al…”
mentioning
confidence: 99%